Role of Hydrothermal Circulation along and above Inherited Basement Structures Relating to Unconformity-Related Uranium Mineralization - Jonathan Poh; Khalifa Eldursi; Patrick Ledru; Philippe Yamato; Guoxiang Chi; Antonio Benedicto (Geofluids)
The reactivation of inherited tectonic structures formed during the Paleoproterozoic Trans-Hudson Orogeny (THO) has played a significant role in generating high-grade unconformity-related uranium deposits in the eastern Athabasca Basin. The role of these tectonic structures is now investigated through a series of two-dimensional hydrothermal numerical models. Two modelling scenarios are considered: (1) models during the THO peak of metamorphism and (2) models with a permeable layer mimicking the presence of the Athabasca Basin, deposited unconformably over the THO basement. In the first scenario, general fluid patterns are strongly affected by the applied permeability configurations. Unidirectional high fluid flow zones (from 10-9 to 10-8 m·s-1) and high thermal gradients (up to 65°C·km-1) can be observed above and within the deep-seated tectonic structures. In the second scenario, well-established fluid convection cells or unidirectional fluid flow zones are observed within the basin layer, with upflow originating from the core of the deep-seated structures, regardless of the applied fluid pressure regime. These results highlight that these deep-seated structures can efficiently transport fluids and heat towards the upper parts of the crust and the basin. In the second scenario, the loci for preore alteration are then evaluated by computing a rock alteration index based on temperature and fluid velocity constraints. These alteration areas reside along and above the deep-seated structures and are potential regions for structural reactivation during mineralization. These results imply that the analysis of the inherited tectonic structures, combined with the alteration regions, can serve as markers for uranium exploration.